1987
DOI: 10.1111/j.1365-2133.1987.tb04922.x
|View full text |Cite
|
Sign up to set email alerts
|

Scheduled and unscheduled DNA synthesis in epidermal cells of hairless mice treated with immunosuppressive drugs and UVB-UVA irradiation

Abstract: The effects of the immunosuppressive drugs azathioprine, prednisolone and cyclosporin A, and UV irradiation on scheduled DNA synthesis, representing mitotic activity, and unscheduled DNA synthesis, representing DNA repair activity, in the skin of hairless mice were determined autoradiographically following intradermal administration of [3H]-thymidine. Azathioprine and prednisolone, and, to a lesser extent, cyclosporin A, were found to impair normal repair of UVR-induced DNA lesions in epidermal keratinocytes. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
13
0

Year Published

1997
1997
2016
2016

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(14 citation statements)
references
References 28 publications
1
13
0
Order By: Relevance
“…However, it was subsequently shown that Azathioprine (Aza) and CS could lower the repair of DNA lesions induced by solar UV radiation (17,18). CS Figure 2).…”
Section: Besides Impairing the Ability Of The Host Immune System To Ementioning
confidence: 99%
“…However, it was subsequently shown that Azathioprine (Aza) and CS could lower the repair of DNA lesions induced by solar UV radiation (17,18). CS Figure 2).…”
Section: Besides Impairing the Ability Of The Host Immune System To Ementioning
confidence: 99%
“…9,56,59,65 Independent of their immunosuppressive effects, there is laboratory evidence that azathioprine and cyclosporine have direct biological effects capable of enhancing UVR-related carcinogenesis. Azathioprine sensitizes DNA to ultraviolet A radiation, 66 reducing the minimal erythema dose in skin cells of treated patients, 67,68 while cyclosporine inhibits DNA repair and apoptosis in ultraviolet B radiation-exposed human keratinocytes. 69,70 However, exposure to either of these agents has not been consistently associated with an increased risk of NMSC.…”
Section: Nonmelanoma Skin Cancermentioning
confidence: 99%
“…A number of European studies report a 27 ± 40% cumulative risk of developing either a basal cell (BCC) or squamous cell cancer (SCC) within the ®rst 20 years following transplantation (Hartevelte et al, 1990;London et al, 1995;McGregor and Proby, 1995). Several mechanisms have been suggested to account for this increase, including chemical carcinogenesis (Lennard et al, 1985;Swann et al, 1996), altered DNA repair (Kelly et al, 1987;Swann et al, 1996) and loss of immune surveillance (Doll and Kinlen, 19970). Human papillomaviruses (HPV) have also been implicated, since other tumours which occur at high frequency in transplant recipients are those associated with a viral aetiology (Morris et al, 1996), including lymphoma, Kaposi's sarcoma and anogential SCC (Birkeland et al, 1995).…”
mentioning
confidence: 99%
“…Such mutations are very rarely observed in sporadic NMSC and the signi®cance of these mutations in the context of post-translant skin cancer is not clear. However, recent suggestions that chronic exposure to azathioprine, and perhaps also to other immunosuppressive drugs used in transplantation, may contribute to carcinogenesis by selecting for clones defective in post-replicative DNA repair requires further study (Kelly et al, 1987;Swann et al, 1996).…”
mentioning
confidence: 99%